Models of cellular regulation - Aguda, B. (Baltazar); Friedman, Avner (Oxford : Oxford University Press, 2008)
This text illustrates the mechanisms and models linking the realms of molecular interactions and biological processes or functions. It addresses the need of mathematical modelers to learn how to formulate models of cellular processes.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cellular control mechanisms -- Mathematical models